What is a "Mafia State" and how is one created?. (2nd November 2022) - McCarthy-Jones, Anthea; Turner, Mark
ABSTRACT: How do corrupt practices evolve into the almost complete criminalization of the state, and what are the conditions necessary for a mafia state to emerge? In this article, we trace Venezuela's political trajectory under President Hugo Chávez and its causal connection to the consolidation of a mafia state under President Nicolás Maduro by identifying critical junctures that occurred under the administrations of Presidents Chávez and Maduro. These critical junctures first laid the foundations for the mafia state, albeit unintentionally, and then allowed and encouraged the criminalization of the state. The incremental abolition of governance institutions started by Chávez and continued by Maduro in the context of dramatic decline in oil production created an ideal environment in which criminal activities could thrive. By the end of this process, Venezuela had evolved into a complex kleptocracy in which no rule of law or institutions were capable of or willing to oppose the executive and its loyal military and irregular force allies. Thus, a mafia state is born.